2019
DOI: 10.1148/radiol.2019181816
|View full text |Cite
|
Sign up to set email alerts
|

Performance and Reading Time of Automated Breast US with or without Computer-aided Detection

Abstract: se of mammography has been shown in randomized controlled trials (1,2) to reduce breast cancer mortality. However, the sensitivity of mammography is poor in women with dense fibroglandular tissue (3,4). As a supplement to mammography, handheld US and automated breast (AB) US can help to improve detection of cancer (5-8). Handheld US is operator dependent, and therefore the experience of the operator is important. At AB US, full coverage of each breast consists of two to five acquisitions (8,9). Each acquisitio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

2
21
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 41 publications
(23 citation statements)
references
References 32 publications
2
21
0
Order By: Relevance
“…A CAD software for 3D ABUS (QVCAD™, QView Medical) has been recently developed and FDA approved [41]. Several studies have been investigating the benefits of concurrent-read CAD systems for interpretation of screening ABUS, and CAD seems to significantly reduce interpretation time, up to 35%, as well as improving diagnostic accuracy [42][43][44]. Another approach to speed up reading is the use of coronal plane only [45], but more work on this is required to ensure that sensitivity does not drop.…”
Section: Computer-aided Detection/diagnosismentioning
confidence: 99%
“…A CAD software for 3D ABUS (QVCAD™, QView Medical) has been recently developed and FDA approved [41]. Several studies have been investigating the benefits of concurrent-read CAD systems for interpretation of screening ABUS, and CAD seems to significantly reduce interpretation time, up to 35%, as well as improving diagnostic accuracy [42][43][44]. Another approach to speed up reading is the use of coronal plane only [45], but more work on this is required to ensure that sensitivity does not drop.…”
Section: Computer-aided Detection/diagnosismentioning
confidence: 99%
“…This diagnostic support system has been approved by the FDA and reported to be useful in the US [47]. Yang et al [48] and Xu et al [49] also demonstrated that CAD systems improve the diagnostic performance for ABUS interpretation (Table 2). CAD, computer-assisted diagnosis; AUC, area under the curve; ABUS, automated breast ultrasound.…”
Section: Object Detectionmentioning
confidence: 99%
“…Additionally, the anatomical planes of interest within the volume can be visualized and reviewed in multiplanar views, including the transverse, sagittal, and coronal planes [12][13][14]. In the last few years, an automated whole breast ultrasound equipment, i.e., automated breast volume scanner (ABVS), has been increasingly used in breast imaging practice, including detection and characterization [11,[15][16][17], and assessment of treatment response after neoadjuvant chemotherapy [18]. Compared with conventional 3D-US, the advantage of ABVS lies in a large field of view, so that the breast can be fully displayed by only two to four-volume scans [11,15,19].…”
mentioning
confidence: 99%